THE DINAMIC OF THE INDEXES OF IMMUNE STATUS OF ELDERLY PATIENTS WITH ODONTOGENIC PHLEGMON OF THE MAXILLOFACIAL REGION ALONG WITH TAKING IMMUNOMODULARY THERAPY - E. V. Fomichyev; B. Yu. Gumilevskiy; A. S. Serbin (Кубанский научный медицинский вестник, 2014)
This article focuses on the problems of increasing the efficiency of complex treatment of odontogenic phlegmon of the maxillofacial region of elderly patients. The results has been presented including clinical and immunology research and treatment of 50 elderly patients with odontogenic phlegmon of the maxillofacial region. It was commited that depression parts of local and general immunity take place. The authors has been shown including in the sheme of traditional treatment of this disease of polyoxidony allows to normalization parts of local and general immunity indices and to enhances the effectiveness and decreases the term of the patients treatment at the hospital.